(Λ,Μ)-Multi Fuzzy Subgroup Of A Group (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we have defined  (λ,μ)- multi fuzzy subgroups of a group G and discussed some of its properties by using  . Also We have defined (λ,μ)-multi fuzzy cosets of a group and proved some related theorems with examples.Mathematics Subject Classification :03F55, 08A72, 20N25, 03E72, 06F35